Gwarowe nazwy wyrobów ze świniobicia w języku mieszkańców kilku wsi rejonu mościskiego - Kostecka-Sadowa, Anna (Slavia Occidentalis, 2023)
The subject of the article is the dialectal names of products prepared after pig slaughter presented against the background of the language spoken by Poles in the south-eastern borderlands. My analyses revolve around the dynamics of change to food names. The aim of the article is to present a selected group of lexemes attributed to one of the subfields of dialectal culinary vocabulary, to draw attention to the meaning of names, their origin and motivation (partly also to the formal shape), as well as to discuss the nomination mechanisms. The research is based on own field materials collected in this area.